2020
DOI: 10.1016/j.clml.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nomogram for Overall Survival in Early Stage Extranodal Natural Killer/T Cell Lymphoma Treated With High-Dose Radiotherapy

Abstract: The prognostic system for early stage extranodal natural killer/T-cell lymphoma, nasal-type (ENKL) treated with high-dose radiotherapy (RT) remains unclear. We developed a nomogram including 4 variables in 81 early ENKL patients treated with high-dose RT. This nomogram could predict 5-year overall survival accurately, which provides a meaningful risk estimate for early ENKL. Background: The aim of this study was to develop a prognostic nomogram for early stage extranodal natural killer/ T-cell lymphoma, nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The infection of Epstein-Barrvirus (EBV) may be closely related to its pathogenesis [ 2 ]. At an early stage of ENKTL, the combination of chemotherapy and radiotherapy prolongs patients’ survival and improves the quality of life [ 3 , 4 ]. However, for advanced refractory ENKTL patients, the efficacy of current treatment is not satisfactory [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The infection of Epstein-Barrvirus (EBV) may be closely related to its pathogenesis [ 2 ]. At an early stage of ENKTL, the combination of chemotherapy and radiotherapy prolongs patients’ survival and improves the quality of life [ 3 , 4 ]. However, for advanced refractory ENKTL patients, the efficacy of current treatment is not satisfactory [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 32 To date, neither an optimal treatment strategy nor a valuable prognostic index has been identified. 5 , 33 Several prognostic models have been used for ENKTL, including IPI, 34 KPI, 13 PINK, and PINK-E. 15 However, these prognostic models for ENKTL are still controversial. Although the IPI systematically predicted the prognosis for aggressive NHL, it failed to properly predict survival outcomes in a few studies of early-stage ENKTL.…”
Section: Discussionmentioning
confidence: 99%
“…ENKTL is a rare subtype of non‐Hodgkin lymphoma with poor outcome, the 5‐year OS rates in large cohort studies range from 30% to 86%, and most studies showed that the rates were less than 50% 4,32 . To date, neither an optimal treatment strategy nor a valuable prognostic index has been identified 5,33 . Several prognostic models have been used for ENKTL, including IPI, 34 KPI, 13 PINK, and PINK‐E 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,30,32 These experimental findings corroborate the clinical correlations of an elevated serum LDH with a poor prognosis and suboptimal tumour response. 13,15,33,34 However, it is unknown if this observed correlation between LDH activity and cancer outcomes is isoenzyme-specific (LDH 1–5). Given that LDH isoenzymes are highly tissue-specific, it is plausible to consider that different isoenzymes could be predictive of tumour response to CT at specific anatomical organs, which could be investigated going forward.…”
Section: Discussionmentioning
confidence: 99%